A REMOTE CONTINUOUS AIR MONITORING SYSTEM FOR MEASURING AIRBORNE ALPHA CONTAMINATION. Issue 2 (12th March 2020) - Morishita, Yuki; Usami, Hiroshi; Furuta, Yoshihiro; Aoki, Katsunori; Tsurudome, Koji; Hoshi, Katsuya; Torii, Tatsuo
Abstract: We developed a remote continuous air monitoring (RCAM) system. The RCAM system consisted of a personal air monitor and a robot. The personal air monitor (poCAMon, SARAD, Germany) had a 400-mm 2 ion-injected silicon detector and a membrane air filter with 25 mmφ. The personal air monitor provides the alpha energy spectra for any measurement time interval. Demonstration measurements were taken underground at the Mizunami Underground Research Laboratory and at a poorly ventilated concrete building. The RCAM system was remotely operated and successfully measured the 222 Rn progeny even though the relative humidity was almost 100%. In the measured alpha spectra, the peaks of 218 Po (6.0-MeV alpha) and 214 Po (7.7-MeV alpha) were clearly identified. Our developed monitor is promising for alpha dust monitoring in a high gamma-ray environment or contaminated areas where a worker cannot safely physically enter.